Are female secondary school teachers in Bangladesh becoming digitally empowered or disempowered? An exploratory analysis of the impact of digital empowerment on professional development - Sharmin, Nahar (Journal of Management and Business Education, 2023)
Differences in access, skills, and usage of digital technology between men and women have resulted in an unequal experience in using digital technology in changing work environments, especially in education, which is expressed as the gender digital divide. This divide serves as a barrier to digital empowerment and tends to be wider in developing countries. However, there is a scarcity of literature on digital empowerment among female teachers at the secondary school level. Therefore, based on Makinen’s (2006) perspective, this study investigated digital empowerment among Bangladeshi teachers with respect to gender-based differences. Data on the four components of digital empowerment mentioned by Makinen were collected using a semi-structured questionnaire from a random sample of 326 respondents, along with the qualitative method of an in-depth interview and focused group discussion from three city corporations: Dhaka, Khulna,and Rajshahi, according to their digital divide rates. The findings reveal that both overall awareness and technical access status are satisfactory. Yet, female teachers lacked significant intrinsic motivation and computer abilities to perform specific tasks. Findings also revealed that empowered women had better levels of professional capabilities, self-confidence, and more Information and Communication Technology (ICT)-based pedagogy. Female teachers should be recognized and encouraged in institutional programs to promote digital empowerment and reduce the digital divide between genders.